Resolving Contradictions in Public Policies on Child Begging: An N- Alectic Approach - Esther Maricela Coello Avilés; Kevin Luis Flores Vega; Keyla Nayely Casquete Cedeño (Neutrosophic Sets and Systems)
This project fills a wicked problem gap with policy assessments relative to child begging—a condition that keeps children in a vulnerable state within the confines of the urban setting—and the literature gap exists because while prior researchers aimed to review child begging policy assessments, none have done so from an dialectic, multidisciplinary, moral and social intersectional perspective. Filling the literature gap relevance is about contribution to the field because many of these policies stem from an otherwise noble cause to either imprison or render assistance to vulnerable children yet fail when a poorly socioeconomic population's public safety gets in the way; thus the policy assessment literature is inconsistent. Therefore, this project utilizes a dialectic approach which champions a new way to analyze predicated legislated issues from conflicting means and solves them through integrated rationales facilitated by dialectical assessment and social policy professionals. Ultimately, findings reveal that such policies rarely attack the causal tenets of abject poverty and inevitable social exclusion by children begging. Therefore, this project contributes to the literature by providing a theoretical approach to reconciliation of conflicting viewpoints and real-world applicability policy, championing a more coherent, inclusive and child-rights educated policy campaign direction with feasible sustainable change implementation.